2020
DOI: 10.1002/cbic.202000343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic‐Code‐Expansion Strategies for Vaccine Development

Abstract: By providing long‐term protection against infectious diseases vaccinations have significantly reduced death and morbidity world‐wide. In the 21 st century, (bio)technological advances have paved the way for developing prophylactic vaccines that are safer and more effective as well as enabled the use of vaccines as therapeutics to treat human diseases. Here, we provide a focused review on the utility of genetic code expansion as an emerging tool for the development of vaccines. Specifically, we discuss how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 109 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Genetic code expansion and ncAAs have also been utilized to generate different types of vaccines, including peptide vaccines such as subunit, conjugated, and live-attenuated vaccines 256,257 . Grunewald et al 258 first demonstrated that incorporating an immunogenic ncAA into a protein of interest could break the immunological tolerance of self-proteins and evoke an immune response in animal models.…”
Section: Peptides Modification By Genetic Code Expansionmentioning
confidence: 99%
“…Genetic code expansion and ncAAs have also been utilized to generate different types of vaccines, including peptide vaccines such as subunit, conjugated, and live-attenuated vaccines 256,257 . Grunewald et al 258 first demonstrated that incorporating an immunogenic ncAA into a protein of interest could break the immunological tolerance of self-proteins and evoke an immune response in animal models.…”
Section: Peptides Modification By Genetic Code Expansionmentioning
confidence: 99%
“…In fact, there are 31 scales that can be related to polarity, with 27 scales that can be considered non-redundant. Closer look shows that these scales can be grouped in a three large groups dependent on the physical phenomenon they are based upon: 2 In this other formula the mean square (MS) value of all 64 codon differences between any two codes are calculated:…”
Section: Choice Of the Polarity Scalementioning
confidence: 99%
“…It is often considered a universal principle or language, a lingua franca , that unites species on the planet into a massive superorganism. Due to the genetic code universality, viruses can be transmitted between different species, as we learned from the outbreaks of viral diseases of animal origin [2] . Another outcome of the code universality is the ability to spread fragments of genetic information between species in the course of the horizontal gene transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic code expansion (GCE) is a biotechnology whereby a non-canonical amino acid (ncAA) could be inserted into proteins through suppressing an artificially introduced stop codon or quadruplet codon with an orthogonal aminoacyl-tRNA synthetase (aaRS)/tRNA pair. 13 After two decades of research and development, 14 GCE is becoming one of the most powerful strategies in protein engineering, and provides unique tools to many research fields, such as bioorthogonal chemistry, 15 artificial enzyme design, 16 biocontainment development, 17 vaccine development, 18 protein/peptide-based drug discovery, 19 and so on.…”
Section: Introductionmentioning
confidence: 99%